MANAJEMEN SUMBERDAYA MANUSIA DALAM PERSPEKTIF ISLAM DAN ELEVANSINYA DENGAN MANAJEMEN MODERN - ., Dhoni Kurniawati (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2018)
This reserach aims to know and analyze the Islamic perspective on human resource. The approach used in this research was library research. The research results ontained : (1) The principle of human resource planning in Islam perspective, is God Almighty makes a plan, God’s plan is very firm, refers to Allah’s instructions is planning, carefully crafted planning, planning accompanied by tawakal. (2) The principle of the procurement of human resources in Islam perspective is the criteria for recruitment of human resources that is strong and trustworthy. (3) The principle of training and  development of human resources in the perspective of Islam, is God commands to seek knowledge, requires knowledge to worship, education and HR training is based on a strong monotheistic foundation. (4) The principle of maintaining human resources in Islam perspective is the provision of appropriate rewards, not giving heavy burdens. (5) The  principle of assessing human resources in Islam perspective is that Islam teaches its people to be serious about working, achieving optimal goals depending on performance.Keywords: Manajemen, Sumberdaya Manusia, Perspektif Islam